PERANCANGAN DESAIN KEMASAN MAKANAN RINGAN BERCIRIKAN BUDAYA LOKAL MINANGKABAU - SUDIANI Yoni
Packaging is a container of goods.With many Forms and uses , eash has different functions and meaning . Recently , there are only few west Sumatra snack packaging which characterizes local Minangkabau culture ,that becomes a problem ,how to design west Sumatra snack packging which characterizes local Minangkabau culture .The purpose of food packging design ,characterizes by local Minangkabau culture ,is giving the impreeeion that regionalism can be recalled by consumers with the presence of these culture elements ,and create a unique and attractive packging. Traditional food packging is needed,so that people or the consumers know these traditional foods.The packging design of tradisional west Sumatra food is applied on snacks ,as commonly used as souvenirs and traditional foods,that can be taken anywhere and durable.In the food packging design ,creation method using 5W+1H method is used ,to analyze the data. The creation of packaged smack, characterizes by the local culture , apples the elements of Minangkabau culture . There are many elements of Minangkabau culture ,but only the selected one is used in the snack packging design ,which is able to represent onther element of Minangkabau culture .snacks packging will use plastic as a primary packaging material , because minang snacks are usually oily , then combined with the paper material to convoy the message by considering aspect of visual communication effectiveness by incorpormation